New Product Technology, Accumulation, and Growth - Khan, Faruk A. (World Bank, Washington, DC, 2012)
This paper asks whether new technological capacity for producing and exporting additional products provides incentives for greater capital accumulation, without being fully reflected in a higher rate of total factor productivity (TFP) growth. Using a highly disaggregated data set of each country's trade flows into the United States, the author constructs a direct and independent measure of technological improvements for each country over time based on the number of new product varieties exported to the United States. The author shows, in a panel data setting, that acquiring the technological capacity for producing new products stimulates more rapid capital accumulation in developing countries, even after holding fixed the rate of TFP growth. His findings provide evidence against the alternative view that technological improvements are essentially unimportant: a view based on the findings of Young (1995) and others that instances of spectacular economic growth have been associated with unspectacular rates of TFP growth. The author provides a model to show how an expansion in the technological capacity for producing additional products can lead to more rapid factor accumulation, without necessarily improving measured TFP. His findings suggest that while rapid accumulation of physical and human capital may have characterized the East Asian growth experience, these gains were stimulated by stellar improvements in technological capacity.